PENERAPAN PENGGUNAAN ABSENSI KARYAWAN MENGGUNAKAN PENGENALAN WAJAH ATAU FACESCAN YANG DITERAPKAN PADA KARYAWAN PERUSAHAAN - Lip Son; Rainal Agus Setiawan; Vennes Owen; Riswanto Riswanto; Muhammad Baharudin; Zulkarnain Zulkarnain; Sabariman Sabariman (Journal of Information System and Technology (JOINT), 2023)
Today's artificial intelligence has helped humans in everyday life. As we know, almost all companies now use the method fingerprint as employee attendance. Therefore, the purpose of this study is to replace the attendance system method fingerprint with a face recognition or attendance system facescan. For this purpose, it is motivated by the current virus pandemic Covid-19 which requires all employees to maintain a distance or practice social distancing. This face recognition attendance consists of 2 stages, namely the face recognition stage and the face detection stage. At the face recognition stage is the process of comparing a face image with a face database, to find a match. At the face detection stage, human faces are taken by digitally scanning 2D photos. At the stage of the test results, the user is asked to try to run the facescan . The user is asked to bring the face closer to the camera on the facescan, then the facescan will detect the user's face and display the user's personal data. Not only that, facescan will display the user's body temperature at the time of detection